Spontaneous pneumothorax in adulthood varicella - Badri, Talel (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Varicella is a generalized viral infection that is generally benign if it occurs in childhood, but it has a severe outcome in adulthood. Pneumonia is the main complication of adulthood varicella and may lead to respiratory failure. Spontaneous pneumothorax is a rarely reported complication during varicella in adult patients. Only one case of spontaneous pneumothorax associated with varicella pneumonia (VP) was published in 1990. We report a new case of pneumothorax in VP.
Keywords: norice; odrasli; pnevmotoraks; varicella zoster